Proposal of a probabilistic reproduction for multi- dimensional assessment of structural behavior and understanding professional ethics: a green technology approach - Eusuf, Muhammad Abu; Abdul Rashid, Khairuddin; Ibrahim, Mansor; Mohit, Mohammad Abdul; Salleh, Nurul Hamiruddin; Salleh, Md. Noor (2013)
It is desirable to verify the structural performance based on a multi-dimensional approach, considering the significant actions the structure in issue could be subjected to during its lifetime assessment. The whole life principle has been introduced into analysis, design and management of structures. The professional have to generate and study novel skills in order to achieve a capability for life sequence on design and predictive or service life management of structure. The novel skills include new approach for analysis, design and management process, durability, performance, service life of materials and structures, reliable methods of computation for control the safety over the service life of structures. Although this reliable method is time dependent and treated as time dependent parameter. For this reason safety margin should maintain effectiveness for total life cycle in order to depend the cost of maintenance works and capitalize the performance and serviceability of the structures.